A study of interlocking directorships in Singapore using UCINET & PAJEK. - Hong, Sook Ming. (2008)
Examines the interlocking directorships among 409 SGX Mainboard listed companies in Singapore in 2003, focusing on the extent of interlocking directorships in SGX Mainboard listed companies, as well as what are the groups or cliques of companies and directors that were formed.